A reference trajectory based discrete time sliding mode control strategy - Bartoszewicz, Andrzej; Adamiak. Katarzyna (Zielona Góra: Uniwersytet Zielonogórski)
This study presents a new, reference trajectory based sliding mode control strategy for disturbed discrete time dynamical systems. The desired trajectory, which is generated externally according to an existing switching type reaching law, determines the properties of the emerging sliding motion of the system. It is proved that an appropriate choice of the trajectory generator parameters ensures the existence of the quasi-sliding motion of the system according to the definition by Gao et al. (1995) in spite of the influence of disturbances.
Keywords: discrete time systems; sliding mode control; reaching law; reference trajectory